Efficacy and safety outcomes in vitamin D supplement users in the fingolimod phase 3 trials - Kira Hongell; Diego G. Silva; Shannon Ritter; Daniela Piani Meier; Merja Soilu-Hänninen (My University, 2022)
BACKGROUND:
Low serum levels of 25-hydroxyvitamin D have been associated with worse outcomes in multiple sclerosis (MS) patients treated with interferon-beta. Association of vitamin D nutrition on the outcomes of other MS therapies has been studied less.
OBJECTIVE:
Whether patients in the phase 3 fingolimod trials using vitamin D supplements have better clinical, MRI and safety outcomes than non-users.
MATERIALS AND METHODS:
Pooled data from phase 3 FREEDOMS trials was analyzed post hoc. Vitamin D use was defined as 'non-users' (n = 562), 'casual users' (n = 157) and 'daily users' (usage 100% time in the study, n = 110).
RESULTS:
Expanded Disability Status Scale change from baseline to month 24, and annual relapse rate and proportion of patients with relapses were similar across the vitamin D user groups. Proportion of patients free of new/enlarging T2 lesions significantly favored vitamin D 'daily users' versus 'non-users'. Mean number of lesions were lower and proportion of patients free of gadolinium-enhanced T1-lesions were higher in the 'daily users'. At month 12, percent brain volume change was significantly lower in the 'daily users' versus 'non-users' and remained low at month 24 (non-significant). Incidence of depression was lower for vitamin D 'daily users' (non-significant).
CONCLUSIONS:
We observed improved MRI outcomes on percent brain volume change and proportion of patients free of new/enlarging T2 lesions, and a trend of less depression in the 'daily users' of vitamin D supplement in patients in the FREEDOMS trials.